2019
DOI: 10.1002/alr.22382
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐17A potentiates interleukin‐13‒induced eotaxin‐3 production by human nasal epithelial cells from patients with allergic rhinitis

Abstract: Background: Interleukin (IL)-17A is involved in the pathogenesis of allergic rhinitis (AR). Increased expression of IL-17A is correlated with disease severity and nasal eosinophilia. However, the molecular mechanisms by which IL-17A contributes to T-helper 2 cytokine IL-13-driven pathology in AR remain unclear. We sought to obtain mechanistic insight into how IL-17A and IL-13 regulate the epithelial production of eotaxin-3 representing eosinophilic inflammation in AR. Methods:Human nasal epithelial cells (HNEC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…2a). Given that IL-13 can induce an inflammatory response in HNEPCs and is commonly used for in vitro studies of AR [19], we employed IL-13 treatment as an experimental model. After utilizing IL-13, we found that FGD5-AS1 expression in HNEPCs was obviously lower than the control group ( p < 0.01), indicating that FGD5-AS1 expression was downregulated in AR cells.…”
Section: Resultsmentioning
confidence: 99%
“…2a). Given that IL-13 can induce an inflammatory response in HNEPCs and is commonly used for in vitro studies of AR [19], we employed IL-13 treatment as an experimental model. After utilizing IL-13, we found that FGD5-AS1 expression in HNEPCs was obviously lower than the control group ( p < 0.01), indicating that FGD5-AS1 expression was downregulated in AR cells.…”
Section: Resultsmentioning
confidence: 99%
“…In a Th2 dominant environment, IL-17 can promote eosinophils survival and degranulation, leading to chronic nasal inflammation Moksliniai darbai ir apžvalgos in allergic rhinitis (41). Besides, IL-17 enhances IL-13 induced STAT6 phosphorylation leading to eotaxin -3 production (42). These factors contribute to eosinophilic inflammation.…”
Section: Th17 and Il-17 In Allergic Rhinitis And Allergic Asthmamentioning
confidence: 99%
“…Increasing evidence indicates that nasal epithelial cell dysfunction may be the major cause of nasal allergic inflammation (9,10). The nasal epithelium is the first barrier against allergen infiltration and epithelial cell-derived cytokine milieu activates different types of immune cell, thereby acting as a master immune regulator in allergic inflammation (11)(12)(13). Thymic stromal lymphopoietin (TSLP) is one of the primary epithelial-derived cytokines in T helper type 2 (Th2) reactions (14).…”
Section: Introductionmentioning
confidence: 99%